Elisa And Mat Tests For Leptospira Interogans Detection From Cattle In Eastern Algeria - Benammar, L; Benseghir, H; Hezil, D; Bouchemla, F; Zaidi, S; Bessas, A; Ghalmi, F (Journal of the Hellenic Veterinary Medical Society, 2025)
Leptospira interrogans is one of the most common infectious organisms worldwide that causes several losses in cattle. As far as we know, few previous studies have focused on Leptospira interrogans infection in cattle from Algeria. This study aimed to assess the prevalence of bovine leptospirosis, identify selected risk factors, and compare two different detection tests. 611 blood samples from 67 cattle farms were collected in six Algerian provinces; Algiers, Boumerdès, Bordj Bou Arreridj, Sétif, Batna, and Souk Ahres. Sera samples were analyzed for the presence of antibodies against five serovars of Leptospira interrogans using a microscopic agglutination test (MAT), using 50% agglutination, at a dilution ≥1: 100 as a cut-off point. A commercial indirect enzyme-linked immunosorbent assay (ELISA) test was used to determine the seroprevalence against L. interrogans serovar Hardjo. Moreover, a survey through breeders’ questionnaires was conducted to identify the potential risk factors of Leptospira interrogans infection. The seroprevalence of L. interrogans infection using MAT in the cows was 17.02% (95% confidence interval [CI]: 14.12- 20.24) and in the farms was 83.58% (95% CI: 59.31-81.99). The most commonly detected serovar was Hardjo 6.71% (95% CI: 4.86-8.99) followed by Icterohaemorrhagiae 5.07% (95% CI: 3.47-7.12). Finally, the last serovar present was the Grippotyphosa 2.78 (95% CI: 1.63-4.42). The comparison between the two serological methods, considering the MAT as the reference test, shows that the PrioCHeck ELISA kit had a sensitivity of 63.4% (95% CI: 48.7-78.2), a specificity of 98.9% (95% CI: 98.1-99.8), and a reliability of 96.6% (95% CI: 95.1-98.0). The kappa coefficient was 0.62, and the McNemar test showed a P = 0.23. Multivariable logistic regression analysis showed that the semi-intensive system was a protective factor against leptospirosis, with an odds ratio of 0.35 (95% CI: 0.16-0.78). The study findings indicate that leptospirosis is a serious issue in farms located in selected provinces in Algeria, with a high incidence rate noted there. The semi-intensive system’s significance as a leptospirosis protective factor is to create control strategies that decrease the probability of infection in both humans and cattle.